Pengaruh Perputaran Kas, Perputaran Piutang dan Perputaran Persediaan Terhadap Rturn On Equity (ROE) (Studi Pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2018-2022) - Alipah, Nurul; Amaniyah, Evaliati (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
Every company must have goals and targets to achieve. However, every company activity that will be carried out always requires funds, both funds to finance operational activities in each of the company's daily activities and funds to invest in the long term. The funds used for business continuity are expected to achieve the company's goals, namely obtaining maximum profits. The profits obtained by a company can be a benchmark for assessing the success or failure of a company's management. This research aims to determine the effect of cash turnover, receivables turnover and inventory turnover on ROE. This type of research is quantitative research. The results of this research are that cash turnover has no effect on ROE. Receivables turnover has an effect on ROE, Inventory turnover has an effect on ROE, Cash Turnover, Receivables Turnover and Inventory Turnover simultaneously have a significant positive influence on ROE.